Penyuluhan dan Pelatihan Pemeliharaan Kesehatan Gigi dan Mulut Kader PKK dan Posyandu Kelurahan Grogol, Kecamatan Grogol Petamburan, Jakarta - Permata Setiana Putri, Tansza; Orliando Roeslan, Moehamad; Putri Sekar Palupi, Anggraeny; Erawati, Jeti; Pratama Sarwono, Aditya; Michelle; Ariefa Putri, Elvinadaya; Aryanti, Reski; Muna Riad, Anastasya (Fakultas Kedokteran Gigi, Universitas Trisakti bekerjasama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2024)
The prevalence of oral health problems in the Jakarta Special Capital Region (DKI Jakarta) according to the Basic Health Research (Riskesdas) results in 2018 was 59.1%. Pericoronitis and periodontal disease are common oral cavity issues. Knowledge about maintaining oral health is a key factor in achieving a good quality of life. To increase public understanding of the importance of dental and oral care, this knowledge program is designed to provide holistic and practical information. Therefore, education in the form of counseling and training is needed by directly engaging with the community to emphasize the importance of dental and oral health care, targeting mothers from the Family Welfare Movement (PKK) and Integrated Health Service Post (Posyandu) cadres in the Grogol sub-district. The results show a significant difference between pre-test and post-test (p < 0.0001). In conclusion, the knowledge of participants improves after receiving counseling and training.